2012
DOI: 10.1186/1939-8433-5-28
|View full text |Cite
|
Sign up to set email alerts
|

A WUSCHEL-related homeobox 3B gene, depilous (dep), confers glabrousness of rice leaves and glumes

Abstract: BackgroundGlabrousness is an important agricultural trait for the practical breeding of rice. In this study, depilous (dep), the gene responsible for glabrous leaves and glumes of rice was identified by map-based cloning.ResultsThe dep gene encodes a WUSCHEL-related homeobox 3B that was fine-mapped to a 22-kb region on the short arm of chromosome 5 using progenies derived from crosses between Koshihikari (pubescent) and GLSL15, an Oryza glaberrima chromosome segment substitution line (glabrous). Complementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…Such morphological differences of the PLgh germplasm (Padi Pohon Batu and IARI 6184B) from a traditional pubescent cultivar (Rondo) have not been reported in previous studies, such as Hu et al (1999), Luo et al (2000), Rutger and Mackill (2001), and Li et al (2010a). Plant leaf pubescence or trichomes play an important role in biotic (insects and diseases stresses [Xu et al, 2002; Pfeiffer et al, 2003; Zhang et al, 2003; Kim et al, 2011]) and abiotic stress (weather and soil stresses) tolerance (Saltveit and Hepler 2004; Du et al, 2009; Angeles‐Shim et al, 2012). Pfeiffer et al (2003) observed a delay of aphid infection in soybean cultivars with high density of pubescence, which functioned as a mechanical barrier to aphid probing.…”
Section: Resultsmentioning
confidence: 99%
“…Such morphological differences of the PLgh germplasm (Padi Pohon Batu and IARI 6184B) from a traditional pubescent cultivar (Rondo) have not been reported in previous studies, such as Hu et al (1999), Luo et al (2000), Rutger and Mackill (2001), and Li et al (2010a). Plant leaf pubescence or trichomes play an important role in biotic (insects and diseases stresses [Xu et al, 2002; Pfeiffer et al, 2003; Zhang et al, 2003; Kim et al, 2011]) and abiotic stress (weather and soil stresses) tolerance (Saltveit and Hepler 2004; Du et al, 2009; Angeles‐Shim et al, 2012). Pfeiffer et al (2003) observed a delay of aphid infection in soybean cultivars with high density of pubescence, which functioned as a mechanical barrier to aphid probing.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, OsWOX3B / DEP , a homologue of OsWOX3A , has been reported to regulate the formation of bristle‐type trichomes in the leaves and glumes (Angeles‐Shim et al ., ). Although they belong to the same subfamily of OsWOX proteins (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…However, RNAi‐mediated downregulation of OsWOX3A produced no visible phenotype (Dai et al ., ). OsWOX3B / DEP has been identified recently by positional cloning and functions in the regulation of trichome formation in leaves and glumes (Angeles‐Shim et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Unlike marginal domain‐specific expression domain of WOX3/PRS (Nardmann et al ; Shimizu et al ), sister WOX3 s are expressed in a complete ring around the initiating phytomer and are then restricted to the phytomer base (Nardmann et al ). In rice, these genes are strongly expressed later on in the intercalary region and nodal vasculature of young internodes (Figure C; Angeles‐Shim et al ), suggesting subfunctionalization of the sister WOX3 clade for the distinctive structures of grasses. However, to date, only the sister WOX3 in rice has been characterized to control trichome formation (Angeles‐Shim et al ; Zhang et al ; Yoshikawa et al ) so the relevance of its expression pattern is unclear.…”
Section: Regulation Of Subapical Proliferationmentioning
confidence: 96%
“…In rice, these genes are strongly expressed later on in the intercalary region and nodal vasculature of young internodes (Figure C; Angeles‐Shim et al ), suggesting subfunctionalization of the sister WOX3 clade for the distinctive structures of grasses. However, to date, only the sister WOX3 in rice has been characterized to control trichome formation (Angeles‐Shim et al ; Zhang et al ; Yoshikawa et al ) so the relevance of its expression pattern is unclear.…”
Section: Regulation Of Subapical Proliferationmentioning
confidence: 96%